2005
DOI: 10.1002/adic.200590032
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of Measurement: Approaches and Open Problems

Abstract: Despite of exhaustive literature information, analysts are still fronting serious problems in estimating the uncertainty of measurement (UOM), mainly because of the intrinsic difficulties in choosing an appropriate approach and/or of an inadequate background in statistics and metrology fundamentals. Sometimes, additional problems, at present under debate, make their efforts even more stressful. In this paper, attention is mainly paid to intra-laboratory estimation of UOM, the most frequent situation. After a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The energy separation of the major excursions in the first derivative of the carbon KLL spectrum varies with the chemical state [13]. It was suggested that the value of this separation in a certain energy range also increases the certainty that the carbon is present as contamination.…”
Section: Example Reasoningmentioning
confidence: 99%
“…The energy separation of the major excursions in the first derivative of the carbon KLL spectrum varies with the chemical state [13]. It was suggested that the value of this separation in a certain energy range also increases the certainty that the carbon is present as contamination.…”
Section: Example Reasoningmentioning
confidence: 99%
“…For example, alkaline treatment of 5-methylamino-4-nitroisoxazole 218 leads to oxime 219 along with methylamine [309]. The process proceeds with initial nucleophilic attack at the 5-position of the isoxazole ring.…”
Section: Reactions With Nucleophilic Reagentsmentioning
confidence: 99%